2011
DOI: 10.1021/jp110016u
|View full text |Cite
|
Sign up to set email alerts
|

Multireference and Multiconfiguration Ab Initio Methods in Heme-Related Systems: What Have We Learned So Far?

Abstract: This work reviews the recent applications of ab initio multireference/multiconfiguration (MR/MC) electronic structure methods to heme-related systems, involving tetra-, penta-, and hexa-coordinate species, as well as the high-valent iron-oxo species. The current accuracy of these methods in the various systems is discussed, with special attention to potential sources of systematic errors. Thus, the review summarizes and tries to rationalize the key elements of MR/MC calculations, namely, the choice of the empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
89
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 196 publications
(375 reference statements)
12
89
0
Order By: Relevance
“…12 Recently, there have been quite some interest in using advanced QM methods to study various CYP reactants, in particular compound I. [14][15][16][17][18] Such calculations show that compound I has a complicated electronic structure, with many low-lying excited states. The results indicate that both pentaradicaloid (with five unpaired electrons) and Fe V states are nearly degenerate (within 40 kJ/mol) with the triradicaloid ground state.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Recently, there have been quite some interest in using advanced QM methods to study various CYP reactants, in particular compound I. [14][15][16][17][18] Such calculations show that compound I has a complicated electronic structure, with many low-lying excited states. The results indicate that both pentaradicaloid (with five unpaired electrons) and Fe V states are nearly degenerate (within 40 kJ/mol) with the triradicaloid ground state.…”
Section: Introductionmentioning
confidence: 99%
“…This is important, because both calculations and experiments have implicated these species in the reaction mechanism of the CYPs and indicated that they may lead to reduced barriers compared to the triradicaloid Fe IV state. 8,14,[18][19][20][21][22] Many different quantum-mechanical (QM) methods have been used to study the geometry, electronic structure, and reactivity of the CYPs, ranging from approximate semiempirical methods to high-level multi-reference and coupled-cluster methods. 3,4,17,18 However, the great majority of the calculations have been performed with density-functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porphyrin-based molecules hold a pivotal position in the chemistry of engineered photoactive organic compounds, and extensive electronic structure calculations of monomeric (15) and oligomeric (16,17) porphyrin molecules, porphyrin structures in biomacromolecules (18,19), and quasi-1D and -2D porphyrin systems with infinite sizes have been carried out (13,14,(20)(21)(22)(23). Most applications involve multiporphyrin arrays, either in linear or in cyclic shape, or dendrimers (24).…”
mentioning
confidence: 99%